Successful Transition to a Market Economy in Vietnam: An Interpretation from Organizational Ecology Theory - Hien Thu Tran; Enrico Santarelli (Global Labor Organization (GLO), 2018)
This paper investigates the rationales for the successful economic transition in Vietnam by applying organizational ecology theory. We claim that Vietnam could achieve a smooth transition because the country preserved the strong institutional capacity of the state in parallel with an instant market liberalization approach. Instead of transforming state-owned firms directly into private-owned firms, the economy produced a population of collectively owned and mixed-ownership enterprises that coexisted with state-owned firms to pave the way for the large-scale emergence of privately owned firms afterward. The mechanism underpinning this transition path lies in the evolution and interaction among three organizational forms during the various stages of the transition. Initially, the new private sector emerges and survives because of receiving “legitimacy spillovers” from the well-legitimized collective and mixed sector that shares some “identity overlap”. Overtime, as the private sector accumulates its constitutive legitimacy it competes with and challenges the existence of the old state and collective sector. Finally, the Schumpeterian “creative destruction” process replaces the old sector with the new dominant sector. Empirically, we test this mechanism using the census data of firms operating in Vietnam during 2000-2010, a period following the “doimoi” policy in 1986 that officially recognized private firms in the constitution and included them in the government's annual statistical coverage. We apply Blundell and Bond's generalized method of moments (GMM) estimation technique and Cox's proportional hazard model to study the interaction effects of economic sectors in terms of profitability and survival respectively.
Keywords: L2; O2; O5; 330; ecology theory; ecological process; ownership type; organizational form; economic sector; transition country; Vietnam